2021
DOI: 10.1063/5.0042086
|View full text |Cite
|
Sign up to set email alerts
|

Direct numerical simulation of the turbulent flow generated during a violent expiratory event

Abstract: A main route for SARS-CoV-2 (severe acute respiratory syndrome coronavirus) transmission involves airborne droplets and aerosols generated when a person talks, coughs, or sneezes. The residence time and spatial extent of these virus-laden aerosols are mainly controlled by their size and the ability of the background flow to disperse them. Therefore, a better understanding of the role played by the flow driven by respiratory events is key in estimating the ability of pathogen-laden particles to spread the infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 37 publications
1
58
0
Order By: Relevance
“…We do not describe in detail the turbulent mechanisms during a cough as this is well explained in the recent literature. 16,30,53,54 However, we note that the larger turbulent eddies that influence the particle transport are resolved through the LES approach which is transient. The particles are transported with the eddies with each small time step.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…We do not describe in detail the turbulent mechanisms during a cough as this is well explained in the recent literature. 16,30,53,54 However, we note that the larger turbulent eddies that influence the particle transport are resolved through the LES approach which is transient. The particles are transported with the eddies with each small time step.…”
Section: Resultsmentioning
confidence: 96%
“…Vortex structures during the cough are characterized by the well-known vortex ring structures generated at the edge of the jet. 16,53 We note that expiratory events such as a cough are pulsatile; however, this study considered a cough as a single pulse. Figure 8 shows the droplet trajectories for each droplet found in the vortex ring structure at 1 s. The trajectories represent the individual droplet motion colored by velocity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3,9 In subsequent direct numerical simulation (DNS) analyses, the ambient relative humidity was also found to significantly increase the droplet evaporation time, 25–27 especially those with a diameter below 30 μ m. 27 Rosti et al 26 found that turbulence increases the lifetime of the droplets, and an underestimation of 100% in droplet evaporation time was reported when the turbulence effects were filtered out. Although reasonable estimates of the horizontal displacement of the exhaled puff can be obtained from reduced-order models, 28,29 gas-phase only DNS of a cough 30 has shown that a large deviation from the predicted values could arise due to difficulties in predicting jet-to-puff transition effects and puff topology in such models, in addition to turbulence itself as discussed previously. Still, despite the in-depth physical insight obtained from DNS concerning small-scale interactions between liquid and gas phases, its significant computational cost hinders both the evaluation of long events and the quantification of event-to-event variations.…”
Section: Introductionmentioning
confidence: 92%
“… Talaat et al (2021) used steady Reynolds-Average Navier–Stokes (RANS) simulations to predict the flow field in the cabin of a Boeing 737 airplane to assess mitigation and safety of air travel. Several recent papers presented detailed analyses of the flow physics of a cough using direct numerical simulation ( Fabregat et al. , 2021 ; Monroe et al.…”
Section: Introductionmentioning
confidence: 99%